Issues of environmental changes and transportation - Parpieva Umida; Najmutdinova Gulnoza; Khaydarov Ilhom; Zakirova Gulnora; Karimova Nodira (BIO Web of Conferences)
Environmental changes, driven predominantly by anthropogenic activities, significantly impact air quality, with the transport sector contributing around 40% of emissions. This paper explores the integration of green logistics and green finance as pivotal strategies to mitigate environmental pollution associated with transportation. The methodology combines research, policy development, public awareness, infrastructure improvements, and stakeholder collaboration to promote sustainable transport solutions. Statistical data highlights the increasing production of vehicles and the harmful emissions they generate, emphasizing the urgent need for effective regulation. Analysis reveals that toxic substances from vehicle exhaust, such as nitrogen oxides and carbon monoxide, pose severe health risks. Recommendations for reducing emissions include enhancing vehicle standards, improving waste treatment technologies, and fostering the use of alternative fuels. The findings underscore the necessity for a comprehensive ecological regulation system in Uzbekistan to safeguard natural ecosystems and improve air quality, illustrating a commitment to sustainable development. This approach aims not only to reduce pollution but also to promote economic growth through green practices, ultimately contributing to a healthier environment for current and future generations.